(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2021)
It is shown that the total dissipative work is exactly given by the sum of two contributions. First by the relative entropy of probability of forward path and its time reversed path and second by the relative entropy of non equilibrium and equilibrium probability distribution at that time. The conclusion is supported using a simple model.